Corporate Responsibility For The Crime Of Money Laundering - Vincentius Patria Setyawan; Itok Dwi Kurniawan (Res Judicata, 2022)
Abstract Legal subjects who commit money laundering crimes consist of legal persons (natuurlijk persoon) and legal entities (recht persoon). The rules regarding the form of accountability for the two legal subjects have been regulated in Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering (hereinafter referred to as the Money Laundering Law). case of Beringin Bangun Utama Limited Company. The purpose of this article is to find out about the regulation of accountability for corruption based on the Money Laundering Law and its implementation in the case of Beringin Bangun Utama Limited Company. This study uses a case approach and a statute approach. The results of the research outlined in this article are the implementation of corporate responsibility in money laundering cases using identification theory, which states that in imposing criminal liability on corporations, law enforcers must be able to show that the perpetrator (actus reus) is an individual legal subject. which is the controller of the corporation. Meanwhile, the element of error (mens rea) in identification theory can be determined if the crime is committed to provide benefits for the subject of corporate law.Keywords: Criminal Liability, Corporate, Money Laundering.